Multiliteracy Pedagogy in Teaching Indonesian Drama Study Course - Een Nurhasanah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The findings of this study describe the learning process of Indonesian Drama Studies courses that were taught using multiliteracy pedagogy. Specifically, the theory used in the study, developed by Kalantzis and Cope (2008), is comprised of the following components: (1) Situated Practice/ Experiencing, (2) Overt Instruction/Conceptualizing, (3) Critical Framing/ Analysing, and (4) Transformed Practice/ Applying. The descriptive qualitative method was employed in this investigation. Participants are selected randomly taken from five different classes and placed into a single class. The research data were collected from students’ attendance, teaching materials, paper studies of drama scripts, and YouTube videos amounted to 12 videos. The play was presented in the form of a short performance. The findings show that drama learning can be achieved through the use of multiliteracy pedagogy. In drama learning, students develop a variety of multiliteracy skills, including reading scripts, rehearsing for performances, and editing videotapes of their performances.